2021
DOI: 10.1186/s12967-021-02751-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of susceptibility loci for cardiovascular disease in adults with hypertension, diabetes, and dyslipidemia

Abstract: Background Hypertension (HTN), diabetes mellitus (DM), and dyslipidemia (DL) are well-known risk factors of cardiovascular disease (CVD), but not all patients develop CVDs. Studies have been limited investigating genetic risk of CVDs specific to individuals with metabolic diseases. This study aimed to identify disease-specific and/or common genetic loci associated with CVD susceptibility in chronic metabolic disease patients. Methods We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Previous notable associations with these ten functional candidates include disease (Parkinson’s disease [ 70 ], hypertrophic cardiomyopathy [ 71 ], ischaemic stroke, diabetes mellitus and coronary artery disease [ 72 ]) anthropometrics (BMI-adjusted waist-hip to ratio, BMI [ 73 ]), blood phenotypes (haemoglobin measurement [ 55 ], red blood cell density, haematocrit [ 57 ], eosinophil count and systolic blood pressure [ 54 ]), lung function (FVC [ 54 ], FEV1 [ 51 ]), and heart and electrocardiography measures (QRS measures [ 52 ], and cardiac arrhythmia [ 53 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous notable associations with these ten functional candidates include disease (Parkinson’s disease [ 70 ], hypertrophic cardiomyopathy [ 71 ], ischaemic stroke, diabetes mellitus and coronary artery disease [ 72 ]) anthropometrics (BMI-adjusted waist-hip to ratio, BMI [ 73 ]), blood phenotypes (haemoglobin measurement [ 55 ], red blood cell density, haematocrit [ 57 ], eosinophil count and systolic blood pressure [ 54 ]), lung function (FVC [ 54 ], FEV1 [ 51 ]), and heart and electrocardiography measures (QRS measures [ 52 ], and cardiac arrhythmia [ 53 ]).…”
Section: Resultsmentioning
confidence: 99%
“…For PA, the functional candidates on 17q21.31 ( MAPT , LRRC37A2 , LRRC37A , KANSL1 , CRHR1 , ARL17A and ARHGAP27 ) and 22q13.2 ( L3MBTL2 ) with a high probability of the same variant driving PA association and expression in the adipose, brain, heart, lung and muscle; have previously been associated with disease (Parkinson’s disease [ 70 ], hypertrophic cardio myopathy [ 71 ], ischaemic stroke, diabetes mellitus and coronary artery disease [ 72 ]) anthropometrics (BMI-adjusted waist hip to ratio, BMI [ 73 ]), blood phenotypes (haemoglobin measurement [ 55 ], red blood cell density, haematocrit [ 57 ], eosinophil count and systolic blood pressure [ 54 ]), lung function (FVC [ 54 ], FEV1 [ 51 ]), and heart and electrocardiography measures (QRS measures [ 52 ], cardiac arrhythmia [ 53 ]). We found PA functional candidates enriched in Parkinson’s and Alzheimer’s disease, noteworthy given their underlying insulin resistance pathology (although the insulin resistance link is controversial for Alzheimer’s disease), idiopathic pulmonary fibrosis, multiple system atrophy and primary biliary cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous notable associations with these ten functional candidates include disease (Parkinson’s disease (70), hypertrophic cardio myopathy (71), ischaemic stroke, diabetes mellitus and coronary artery disease (72)) anthropometrics (BMI-adjusted waist hip to ratio, BMI (73)), blood phenotypes (haemoglobin measurement (55), red blood cell density, hematocrit (57), eosinophil count and systolic blood pressure (54)), lung function (FVC (54), FEV1 (51)), and heart and electrocardiography measures (QRS measures (52), cardiac arrhythmia (53)).…”
Section: Resultsmentioning
confidence: 99%
“…For PA, the functional candidates on 17q21.31 ( MAPT, LRRC37A2, LRRC37A, KANSL1, CRHR1, ARL17A , and ARHGAP27 ) and 22q13.2 ( L3MBTL2 ) with a high probability of the same variant driving PA association and expression in adipose, brain, heart, lung and muscle, have previously been associated with disease (Parkinson’s disease (70), hypertrophic cardio myopathy (71), ischaemic stroke, diabetes mellitus and coronary artery disease (72)) anthropometrics (BMI-adjusted waist hip to ratio, BMI (73)), blood phenotypes (haemoglobin measurement (55), red blood cell density, hematocrit (57), eosinophil count and systolic blood pressure (54)), lung function (FVC (54), FEV1 (51)), and heart and electrocardiography measures (QRS measures (52), cardiac arrhythmia (53)). We found PA functional candidates enriched in Parkinson’s and Alzheimer’s disease, noteworthy given their underlying insulin resistance pathology (although the insulin resistance link is controversial for Alzheimer’s disease), idiopathic pulmonary fibrosis, multiple system atrophy and primary biliary cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…29) Actually, hypertension, diabetes, or dyslipidemia has been considered to be a risk factor for CAD. 30) A previous study has revealed 225 DE lncRNAs and 473 DE mRNAs in the submandibular gland of rats with spontaneous hypertension compared with that of Wistar-Kyoto rats. 31) As an obesity-related gene, FAIM2 is regulated by nutritional state and the methylation levels of the FAIM2 promoter are significantly associated with obesity.…”
Section: Discussionmentioning
confidence: 99%